The Language Production of Monolingual Children and Multilingual Children: A Comparative Study of Psycholinguistics - Claudya Benesa Siagian; Bernieke Anggita Ristia Damanik (Journal of Translation, Linguistics and Literature, 2024)
This study aims to determine the comparison of language production in monolingual and multilingual children. In comparing these two studies, two previous studies will be compared, namely research from Murni Mahmud, et al. 2022. Language Production Of Children Aged 6 Years Old: A Psycholinguistics Study and Maria Klara, et al. Language Production among Multilingual Children: Insights on Code Mixing. In the comparison carried out, it was found that monolingual children had obstacles in thinking in composing to say what was on their minds, while multilingual children tended to accidentally speak in mixed languages, but the obstacle was that sometimes the person they were talking to did not understand the language of the speaker.